A rare case of isolated tubercular epididymitis - Kannur, Malappa Shivappa; Hegde, Suraj; Yeshwanth, Sunil Kumar; Tejaswi, K. Venkata (International Surgery Journal, 2020)
Isolated tuberculous epididymitis (ITE), defined as tuberculous epididymitis without clinical signs of kidney. Here we present a middle-aged man who presented with swelling in the right scrotum since, 45 days. On clinical examination, mild tenderness was noted in the right scrotal region, a course of oral antibiotics was started but again patient presented with same complaints after 15 days. Fine needle aspiration cytology of testicular swelling was performed which was confirmatory of tuberculous epididymitis. The patient was advised anti-tuberculosis treatment, which he continued for a duration of 6 months. Following the anti-tubercular treatment, there was no evidence of recurrence.